2011
DOI: 10.1111/j.1755-3768.2011.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii protects against H2O2‐induced apoptosis in ARPE‐19 cells through the transcriptional regulation of apoptotic elements and downregulation of the p38 MAPK pathway

Abstract: ABSTRACT.Purpose: Toxoplasmosis, which is caused by the protozoan parasite Toxoplasma gondii, can lead to severe visual impairment. T. gondii inhibits or delays programmed cell death caused by various apoptotic triggers; however, the mechanisms involved in the T. gondii-induced suppression of apoptosis in retinal cells have not been analysed in detail. Methods:We investigated the role of T. gondii infection in H 2 O 2 -induced apoptosis in human retinal pigment epithelial cells (ARPE-19) by monitoring the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Activation of the MAPK family is redox sensitive (Choi et al. ), and the MAPK signalling is involved in acrolein‐induced cell toxicity (Tanel & Averill‐Bates ; Moretto et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the MAPK family is redox sensitive (Choi et al. ), and the MAPK signalling is involved in acrolein‐induced cell toxicity (Tanel & Averill‐Bates ; Moretto et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, pathogenesis of lesions at outer BRB was investigated by using T . gondii -infected cells instead of tachyzoites that were commonly used in other studies to directly infect RPE [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that H 2 O 2 , another oxidative agent, induces RPE cell death characterized by the production of ROS [47][49], cytochrome c release [50], [51], DNA fragmentation [49], [51], Annexin V-binding [52], TUNEL-staining [50], and caspase-3 activation [47], [49], [51], [53]. RPE cells can be protected from H 2 O 2 -induced cell death by treatment with antioxidants such as ascorbate (vitamin C) [54], N-acetylcysteine [47], and quercetin [55].…”
Section: Discussionmentioning
confidence: 99%